2012
DOI: 10.5137/1019-5149.jtn.6497-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple extracranial metastases from secondary glioblastoma: a case report and review of the literature

Abstract: Glioblastoma represents extreme anaplasia in astrocytic tumors. In spite of this aggressiveness, extracranial metastasis of glioblastoma is very rare and has been documented in only a few patients in the literature. In this article, a 30-year-old woman with secondary glioblastoma associated with extracranial distant metastasis was presented. In September 2008, an intracranial lesion in the left frontal region was diagnosed by magnetic resonance imaging (MRI) after admission to the hospital by headache and seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 6 publications
(6 reference statements)
1
21
0
Order By: Relevance
“…The lungs are the most common site. [3,4] Pulmonary metastasis of GBM was observed in both of the cases currently presented.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The lungs are the most common site. [3,4] Pulmonary metastasis of GBM was observed in both of the cases currently presented.…”
Section: Discussionmentioning
confidence: 71%
“…The treatment modalities for primary tumors and metastases involve surgical procedures and adjuvant chemoradiotherapy directed at the primary tissue. [4] It is thought that the use of chemotherapy after the development of metastasis is particularly helpful to improving survival. Chemotherapy was applied with RT for lung metastasis of GBM in both case 1 and case 2. posed, but the mechanism of metastasis has not yet been fully explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…performed a literature review, finding a total of 88 reported cases of GB extracranial metastases [8] . Previous studies had described an average detection time of extracranial metastasis of 8.5 months and a time to death of 1.5 months [9] . In the current case, the metastasis detection time was 1.5 months with a time to death of 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Parotid and cervical lymph nodes [50] Kim et al (2014) 1 Bone, pleural effusion [46] Hamilton et al (2014) 3 Lung, pleura, masticator muscles, parotid and vertebra [7] Takanen et al Cervical lymph nodes and ischium [52] Blume et al (2013) 1 Lung and pulmonary lymph nodes [53] Mujtaba et al (2013) 1 Cervical lymph nodes [54] Guo et al (2012) 1 Subcutaneous metastases [55] Dawar et al (2012) 1 Subcutaneous metastases, diffuse lymph node involvement, pulmonary involvement and pleural effusion [56] Ginat et al (2013) 1 Scalp metastasis [57] Seo et al (2012) 1 Left neck [58] Schonsteiner et al (2011) 1 Liver [59] Armstrong et al (2011) 1 Scalp and temporalis muscle [60] ECMGBM Review informahealthcare.com a 39-year-old male who underwent surgical resection with adjuvant radiotherapy for a high-grade pleomorphic glial neoplasm consistent with GBM. Two years after surgery, the patient developed recurrent intracranial GBM at which time a CT of the abdomen revealed a 9 Â 13 Â 10 cm mass in the false pelvis and a 5 Â 4 Â 3 cm mass within the mesentery as well as a 2 cm mass in the head of the pancreas.…”
Section: Cases Described In Textmentioning
confidence: 98%